Field performance of improved cowpea varieties under conditions of natural infestation by the parasitic weed Striga gesnerioides - Kamara, A.Y.; Chikoye, David; Ekeleme, F.; Omoigui, L.O.; Dugje, I.Y. (Informa UK Limited, 2008)
Cowpea is an important food crop in the dry savannas of West and Central Africa because of its high protein content. Yields are, however, considerably reduced by the parasitic angiosperm Striga gesnerioides. Field trials over 2 years in two localities in northeast Nigeria evaluated the performance of diverse cowpea varieties under conditions of natural infestation by Striga. Grain yield was higher in Tilla than in Damboa where the higher Striga infestation may be caused by the lower rainfall and the sandy nature of the soils. Two varieties (IT97K-499-35 and IT90K-82-2) were confirmed to be resistant to Striga. Yield gain from IT97K-499-35 over the local variety ranged from 30% in Tilla in the northern Guinea savanna to 126% in Damboa in the Sudan savanna. The local variety Borno Brown and two improved varieties were found to be as susceptible to Striga as the susceptible control, TVX-3236, and therefore may not be recommended for cultivation in areas where Striga infestation is a problem. One variety, reported previously to be resistant to one or two races of Striga supported moderate levels of emerged Striga, suggesting that it is not totally resistant to the Striga race in the two localities. However, it produced grain yields that were comparable to the resistant varieties in the locality that was most infested, suggesting that it is tolerant to Striga. There are concerns about the adoption potential of the Striga-resistant variety IT97K-499-35 because of its medium-sized white seeds. Farmers in this zone prefer large-seeded brown cowpea. We recommend that efforts be made to develop Striga-resistant varieties that satisfy end-user preferences.